Quality in the technical performance of screening flexible sigmoidoscopy: recommendations of an international multi-society task group. Issue 6 (11th May 2005) - Levin, T R; Farraye, F A; Schoen, R E; Hoff, G; Atkin, W; Bond, J H; Winawer, S; Burt, R W; Johnson, D A; Kirk, L M; Litin, S C; Rex, D K
Abstract : Background: Flexible sigmoidoscopy (FS) is a complex technical procedure performed in a variety of settings, by examiners with diverse professional backgrounds, training, and experience. Potential variation in technical quality may have a profound impact on the effectiveness of FS on the early detection and prevention of colorectal cancer. Aim: We propose a set of consensus and evidence based recommendations to assist the development of continuous quality improvement programmes around the delivery of FS for colorectal cancer screening. Recommendations: These recommendations address the intervals between FS examinations, documentation of results, training of endoscopists, decision making around referral for colonoscopy, policies for antibiotic prophylaxis and management of anticoagulation, insertion of the FS endoscope, bowel preparation, complications, the use of non-physicians as FS endoscopists, and FS endoscope reprocessing. For each of these areas, continuous quality improvement targets are recommended, and research questions are proposed.